2018
DOI: 10.1111/eva.12619
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive deletion in resistance gene duplications in the malaria vector Anopheles gambiae

Abstract: While gene copy‐number variations play major roles in long‐term evolution, their early dynamics remains largely unknown. However, examples of their role in short‐term adaptation are accumulating: identical repetitions of a locus (homogeneous duplications) can provide a quantitative advantage, while the association of differing alleles (heterogeneous duplications) allows carrying two functions simultaneously. Such duplications often result from rearrangements of sometimes relatively large chromosome fragments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 65 publications
(107 reference statements)
3
42
0
Order By: Relevance
“…After these two mutations, the joint duplication-280S resistance haplotype introgressed from A. gambiae into A. coluzzii (Figures 8 and 9). This A. gambiae origin is consistent with earlier studies of Ace1 variation in West African locations, which generally reported higher frequencies of 280S (Djogbénou et al 2008;Dabiré et al 2009;Essandoh et al 2013) and CNVs (Assogba et al 2018) in A. gambiae than in A. coluzzii, as one would expect if they had a longer evolutionary history in the former. Whilst previous studies had suggested that the similarity of 280S haplotypes in A. coluzzii and A. gambiae was due to inter-specific introgression (Djogbénou et al 2008;Essandoh et al 2013;, they were focused on partial sequencing of the Ace1 gene and could not assess the relationship between introgression and the wider duplicated region (ca.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…After these two mutations, the joint duplication-280S resistance haplotype introgressed from A. gambiae into A. coluzzii (Figures 8 and 9). This A. gambiae origin is consistent with earlier studies of Ace1 variation in West African locations, which generally reported higher frequencies of 280S (Djogbénou et al 2008;Dabiré et al 2009;Essandoh et al 2013) and CNVs (Assogba et al 2018) in A. gambiae than in A. coluzzii, as one would expect if they had a longer evolutionary history in the former. Whilst previous studies had suggested that the similarity of 280S haplotypes in A. coluzzii and A. gambiae was due to inter-specific introgression (Djogbénou et al 2008;Essandoh et al 2013;, they were focused on partial sequencing of the Ace1 gene and could not assess the relationship between introgression and the wider duplicated region (ca.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, our genome-wide analyses would only capture pre-existing variants that were enriched in the resistant specimens. Ace1 mutations and duplications, which cause cross-resistance with previously employed insecticides (Djogbénou et al , 2008Essandoh et al 2013;Edi et al 2014a;Assogba et al 2015Assogba et al , 2016Assogba et al , 2018, fit this definition and are sufficient to sustain high levels of resistance. However, future analyses on recent collections from populations subjected to regular pirimiphos-methyl-based IRS may reveal additional mechanisms more specifically selected by this insecticide.…”
Section: Genetic Basis Of Pirimiphos-methyl Resistance In a Coluzziimentioning
confidence: 97%
See 3 more Smart Citations